Evaluation of Nonspecific Low Back Pain Using a New Detailed Visual Analogue Scale for Patients in Motion, Standing, and Sitting: Characterizing Nonspecific Low Back Pain in Elderly Patients. (18th November 2012) - Aoki, Yasuchika; Sugiura, Shiro; Nakagawa, Koichi; Nakajima, Arata; Takahashi, Hiroshi; Ohtori, Seiji; Takahashi, Kazuhisa; Nishikawa, Satoru
Abstract : Because we have a clinical impression that elderly patients have low back pain while in motion and standing, but less pain when sitting, we investigate characteristics of nonspecific low back pain (NSLBP), using a new detailed visual analog scale (VAS) scoring system. One hundred eighty-nine patients with NSLBP were divided into an elderly group (≥65 years old, n = 56 ) and a young group (<65 years old, n = 133 ). Low back pain was evaluated by a traditional VAS scoring system, the Oswestry Disability Index (ODI), and a new detailed VAS scoring system in which pain is independently evaluated in three different postural situations (in motion, standing, and sitting). No significant differences were observed in traditional VAS and ODI scores between the two groups. The results of the detailed VAS showed no significant differences between the two groups while in motion and standing. However, the elderly group showed significantly lower VAS score while sitting compared to the young group. In this study of the first use of a new detailed VAS scoring system, differences in characteristics of NSLBP between elderly and young patients were successfully detected. This minor modification of the traditional VAS may be useful for characterizing and evaluating low back pain.